Functional properties of nonwovens as an insulating layer for protective gloves - Gorjanc, Dunja Sajn (Wydawnictwo Politechniki Łódzkiej, 2022)
The basic aim of research presented here is to analyse the influence of the incorporated microporous membrane and the technology of needling process on the functional properties of nonwovens developed as an insulating layer for protective gloves. The studied nonwovens are produced with carded web formation and mechanically bonded with needle bonding. The nonwovens studied contain a microporous membrane of PES with a thickness of 20 μm (samples ST and STL). The experimental part of the present work deals with the mechanical properties: Breaking stress and elongation as well as elastic recovery after cyclic loading. The permeability properties (air permeability) and thermal conduction are also analysed in the experimental part. Research results show that the samples ST and STL, which contain a microporous PES membrane, have a higher breaking stress than the samples T and TL without the microporous PES membrane. Samples ST and STL also show higher values of breaking elongation than samples T and TL. Samples ST and STL are mechanically bonded to the lamella plate using forked needles and therefore have a structured (ribbed) shape that affects the improved mechanical properties. The TL and STL samples, which contain a microporous PES membrane, have higher elastic recovery and lower air permeability than the T and TL samples.
Keywords: nonwoven fabrics; protective gloves; mechanical properties; elastic properties; air permeability; włókniny; rękawice ochronne; właściwości mechaniczne; właściwości elastyczne; przepuszczalność powietrza